2018
DOI: 10.1590/0100-6991e-20181616
|View full text |Cite
|
Sign up to set email alerts
|

Influence of advanced age on postoperative outcomes and total loss following breast reconstruction: a critical assessment of 560 cases

Abstract: in selected patients, breast reconstruction can be considered safe; most documented complications were limited and could be treated conservatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 28 publications
(47 reference statements)
1
11
0
1
Order By: Relevance
“…13,40,41 Although a few studies have discussed IBR in young patients, ours is the first to stratify results according to implant placement location. 16,42 Prepectoral reconstruction has the advantage of sparing patients’ muscle-related complications, which can be especially beneficial in this younger higher risk population. 2629 Although concerns such as rippling and capsular contracture are potential feared complications of prepectoral reconstruction, in recent practice, this has been avoided with the introduction of ADM and fat grafting.…”
Section: Discussionmentioning
confidence: 99%
“…13,40,41 Although a few studies have discussed IBR in young patients, ours is the first to stratify results according to implant placement location. 16,42 Prepectoral reconstruction has the advantage of sparing patients’ muscle-related complications, which can be especially beneficial in this younger higher risk population. 2629 Although concerns such as rippling and capsular contracture are potential feared complications of prepectoral reconstruction, in recent practice, this has been avoided with the introduction of ADM and fat grafting.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that advanced age was not a predictive risk factor for SSC. Conversely, Matsumoto et al 10 in a retrospective study evaluating the effect of advanced age in breast reconstruction, demonstrated that patients older than 60 years had a 1.6 times greater chance of surgical wound complication than the younger patients. There are several limitations to this study similar to retrospective studies using a large database.…”
Section: Discussionmentioning
confidence: 98%
“…However, the rate of surgical site complications in autologous breast reconstruction has been reported in previous studies as high as 49%. 7 - 10…”
Section: Discussionmentioning
confidence: 99%
“…In a study done by Matsumoto et al breasts were divided into three age groups based on the World Health Organization (WHO) classifications [38]. Out of the 153 patients who were in the young group, 63 (41%) had complications [38].…”
Section: Discussionmentioning
confidence: 99%
“…A limited number of studies have assessed the outcomes and complications of IBR in this young group of patients [27,38,39]. Herein, we present our institution’s experience with two-staged, implant-based breast reconstruction, whether immediate or delayed, following either prophylactic or therapeutic mastectomy in patients younger than 40 years of age.…”
Section: Introductionmentioning
confidence: 99%